DIGITAL LITERACY TRAINING: FOSTERING TOLERANCE VALUES IN SOCIAL MEDIA FOR STUDENTS OF SMK PGRI 3 TLOGOMAS - Zakiyah, Millatuz; Emi Setyaningsih; Albar Adetary Hasibuan; Mohamad Anas (UPT. PKM UB, 2022)
Social media is the main source of information and advice for millennials. Social media interactions and the massive development of digital technology have proven to be black holes, but at the same time offer opportunities to make things easier for society. One of the negative impacts of using social media is the fading of tolerance values ​​because SARA content has penetrated and flooded our social media. It is in this context that UPT PKM carries out community service through Digital Literacy Training, where one of the pillars is a digital culture that focuses on knowledge of tolerance values ​​as the basis for digital skills in the life of a diverse society. Digital Literacy Training was held at SMK PGRI 3 Tlogomas, Malang. This event lasts for 2 days, namely on 2 and 3 August 2022. This activity is intended for students who are in the early semester intending to increase their skills and digital intelligence in social media based on tolerance values. There are several things that we do in the community service event, namely strengthening the understanding of tolerance values ​​based on Nusantara culture (Pancasila values) through lecture and discussion methods. Then the students were also invited to understand the digital culture, and then they were persuaded to color social media with content that contained tolerance. The results of community service for two consecutive days can at least increase students' understanding and awareness of the importance of tolerance values ​​in the real world and the virtual world.